Chaos theory and some nursing considerations - Vicenzi, Angela E (Nursing Science Quarterly, 1994)
The alleged synthesis of nursing and public health has not produced the expected community-as-client emphasis. Public health is characterized as disease-focused, with masculine domination, using a causal model. The explanatory model of chaos challenges nurses to reexamine nursing's theoretical base by questioning assumptions associated with linear thinking. The selected chaotic concepts of aperiodicity, attractors, sensitive dependence on initial conditions, phase space, and fractals are discussed here. Each concept's connection to physics and mathematics is cited and considerations for nursing science are outlined. Conclusions include redefining health, nursing, and community in chaotic terms and renaming nursing practice, which has this aperiodic and holistic paradigm, as ecologic health nursing.
14 citations (Crossref) [2023-10-31] Citation Key Alias: lens.org/119-144-108-349-30X tex.type: [object Object]
Keywords: Chaos Theory; Community Health Nursing; Fractals; Human; Models; Nursing; Nonlinear Dynamics; Rogers; Thinking; article; dept.nur; fractal analysis; human; model; nonlinear system; nurse; thinking